(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
The existence of a low permeability barrier acts as a geological discontinuity in oil reservoirs. The presence of such discontinuities could alter the flow of injected hot water in the formation and would significantly influence the hot water flooding projects. The aim of the present work is to demonstrate the influence of a low permeability barrier on hot water flooding performance. For this purpose, we have formulated a numerical model by coupling energy transport and multiphase fluid flow models under non-isothermal conditions. The influence of the horizontal and vertical arrangement of the low permeability barriers in a reservoir formation is investigated. The low permeability barrier has a significant effect on the oil recovery when it is located closer to the injection well; subsequently, the production performance of oil recovery is improved by shifting the low permeability barrier towards a production well. The spatial (location) shift of the low permeability barrier towards the production well reduces its effect on the hot water flooding performance, and in turn, cumulative oil production improves. The cumulative oil produced is found to be 344.14 m3 in 200 days when the low permeability barrier is situated near the production well during hot water flooding, which is improved by 2.23% and 6% with respect to low permeability located at the middle of the reservoir, and closer to the injection well, respectively. The pressure buildup decreases at the injection well with the presence of a low permeability barrier near the injection well. The low permeability barriers present at a slight offset location from the middle of the reservoir in the vertical direction provide a better cumulative oil production than the low permeability barrier arranged with no offset condition and fully offset condition in the reservoir. The cumulative oil produced is found to be 341 m3 in 200 days when the low permeability barrier is present at a slightly offset condition in the middle of the reservoir, which is improved by 1.30% and 1.24% with respect to no offset condition and fully offset condition, respectively. The present study can provide the pathways for the future investigation of low permeability barriers for hot water flooding.